2016
DOI: 10.3389/fpls.2015.01218
|View full text |Cite
|
Sign up to set email alerts
|

Expansion and Function of Repeat Domain Proteins During Stress and Development in Plants

Abstract: The recurrent repeats having conserved stretches of amino acids exists across all domains of life. Subsequent repetition of single sequence motif and the number and length of the minimal repeating motifs are essential characteristics innate to these proteins. The proteins with tandem peptide repeats are essential for providing surface to mediate protein–protein interactions for fundamental biological functions. Plants are enriched in tandem repeat containing proteins typically distributed into various families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
118
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(122 citation statements)
references
References 162 publications
4
118
0
Order By: Relevance
“…Domain combination and convergence and divergence of protein domains could be driven by sub-and/or neofunctionalization of duplicated genes upon gene or genome duplications (Lynch and Conery, 2000;Taylor and Raes, 2004;Gough, 2005;Vogel and Morea, 2006). LRR domain-containing proteins, for example, are thought to be associated with the plant's response to stress adaptation and tolerance (Schaper and Anisimova, 2015;Sharma and Pandey, 2016). Genes encoding proteins with a double Nictaba domain have been identified in three nonrelated species (S. bicolor, G. max and S. lycopersicum), but this could be the result of independent domain reorganizations within the different linages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Domain combination and convergence and divergence of protein domains could be driven by sub-and/or neofunctionalization of duplicated genes upon gene or genome duplications (Lynch and Conery, 2000;Taylor and Raes, 2004;Gough, 2005;Vogel and Morea, 2006). LRR domain-containing proteins, for example, are thought to be associated with the plant's response to stress adaptation and tolerance (Schaper and Anisimova, 2015;Sharma and Pandey, 2016). Genes encoding proteins with a double Nictaba domain have been identified in three nonrelated species (S. bicolor, G. max and S. lycopersicum), but this could be the result of independent domain reorganizations within the different linages.…”
Section: Discussionmentioning
confidence: 99%
“…Protein domain rearrangements are driven by evolutionary events such as duplication, fusion, fission and domain loss, and play an essential role in the evolution and expansion of multi-domain proteins (Kummerfeld and Teichmann, 2005;Weiner et al, 2006;Moore et al, 2008;Moore and BornbergBauer, 2012). Therefore, protein domains are considered discrete evolutionary units and could be related to plant adaptation and tolerance to variable environmental conditions (Yang and Bourne, 2009;Sharma and Pandey, 2016). The plant lectin family comprises all proteins that specifically bind carbohydrates.…”
Section: Introductionmentioning
confidence: 99%
“…A direct relationship exists between ankyrin repeat-containing proteins and plant development and growth. However, few studies have demonstrated a regulatory role of ANK during stress conditions (Sharma and Pandey, 2016). This interaction network suggests a role of AKR2 in plant ROS scavenging and metabolism.…”
Section: Genes Induced In the Tolerant Cultivarmentioning
confidence: 99%
“…Many other candidate genes were identified that are associated with the variation of number of pods per plants. Among the candidate genes, basic helixloop-helix (bHLH) DNA-binding superfamily protein that is involved in the development and dehiscence of seed and pod (Hudson and Hudson, 2015), protein kinase superfamily protein is involved in pollen abortion (Radchuk et al, 2006), pyruvate kinase family protein associated with early embryo abortion of flower (Zhang et al, 2014), ARM repeat superfamily protein is involved in self-incompatibility and reduction of pod number (Sharma and Pandey, 2016), chaperone DNAJ-domain superfamily protein is involved in male sterility (Yang et al, 2009), DNAJ heat shock Nterminal domain-containing protein that increases tolerance to heat and prevents fruit drop (Zhao et al, 2015), prolinerich family protein associated with flower and pod development (Giorno et al, 2013), adenine nucleotide alpha hydrolases-like superfamily protein is involved in male sterility (Mok and Mok, 2001), homeodomain-like protein regulates anther dehiscence (Wilson et al, 2011), cytochrome P450 is involved in the pollen tube development and fertilization (Zhao et al, 2015), pyruvate kinase family protein found associated with early embryo abortion (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%